High-temperature-resistant PI lithium battery porous diaphragm and preparation method thereof, secondary battery
Patent Information
- Application Number
- CN202511078709.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-08-01
AI Technical Summary
然而,聚烯烃膜的缺点在于:(1)热稳定性较差,易在高温下分解和变形;(2)对电解液的浸润性较差,导致电池的倍率性能和循环性能降低;(3)机械强度较低,发生异物穿刺时容易导致电池短路失效
(1)加工性能优良:通过PAA链段中的螺环基团、双环原酸酯基团与第二螺环化合物进行光交联反应,再进行亚胺化处理,得到交联的耐高温PI锂电多孔隔膜。交联后的力学性能得到提高,并且孔洞得到固定。在后续的干燥、剥离、卷绕等工序中,交联后的隔膜不易破损,能承受更大的牵引张力和剥离力。交联使PAA膜在亚胺化处理的过程中体积收缩效应减小,有利于孔洞和隔膜的完整。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a high-temperature resistant PI lithium battery porous separator, its preparation method, and a secondary battery. Background Technology
[0002] Lithium-ion batteries have wide applications in consumer electronics, electric vehicles, and energy storage systems. The lithium battery separator is a crucial component of lithium batteries and one of the key materials with technological barriers in the industry chain. Currently, lithium battery separators are usually made of thin-film polyolefin porous membranes, which have good electronic insulation and resistance to electrolytes. However, polyolefin membranes have the following disadvantages: (1) poor thermal stability, which makes them prone to decomposition and deformation at high temperatures; (2) poor wettability to electrolytes, which leads to a decrease in the rate performance and cycle performance of the battery; and (3) low mechanical strength, which makes the battery prone to short-circuit failure when punctured by foreign objects.
[0003] Polyimide (PI), as a high-performance polymer material, has excellent mechanical strength, thermal stability, and chemical inertness, and can be used as a lithium battery separator. The existing production methods of PI separators are mainly electrospinning and phase separation. Among them, the separator prepared by electrospinning has high porosity but poor mechanical properties and low film formation efficiency, which is not conducive to large-scale industrial production. The phase separation method is simple to operate and suitable for large-area film formation, but it also has the following defects: (1) the linear structure of PI leads to insufficient mechanical properties of the separator; (2) the thermal stability of linear PI still needs to be improved; (3) polyamic acid (PAA) is an intermediate product for preparing PI separators. The PAA wet film is soaked in casting solution to form pores, dried and peeled off from the base film, and then wound into rolls to obtain the PAA film. During drying, due to further evaporation of solvent, thin PAA coating and poor mechanical properties of linear PAA, the pores in PAA are prone to deformation and collapse, affecting the uniformity of pore shape and pore size, and thus affecting the porosity of the separator. In severe cases, the PAA layer is damaged due to the different volume changes of PAA and base film under heat, and the diaphragm cannot be completely peeled off; (4) The diaphragm needs a large porosity and good mechanical strength, but it is difficult to achieve both porosity and mechanical properties simultaneously; (5) When peeling and winding the PAA film, a device that provides traction tension is used to make it flat, and the rolled PAA film is under stress, making the diaphragm easy to break during winding; (6) The rolled PAA film is transformed into a PI diaphragm by heating. During the imidization process, as amide bonds are generated, the volume of the diaphragm shrinks further, causing the pores to shrink or collapse, resulting in a decrease in porosity and mechanical properties. In addition, PI material is a relatively brittle polymer. Due to the use of a traction tension device in the winding process, the rolled PAA film has internal stress, which can easily lead to the breakage of the rolled PI diaphragm.
[0004] Therefore, there is an urgent need to provide a high-temperature resistant PI lithium battery porous membrane and its preparation method that can solve the above-mentioned defects. Summary of the Invention
[0005] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a high-temperature resistant PI lithium-ion battery porous membrane, its preparation method, and a secondary battery. The preparation method, by adding spirocyclic compounds and bicyclic orthoesters to the polymerization reaction as sites for subsequent photocrosslinking and curing, facilitates the fixation of pores in the PI membrane and improves the material's mechanical properties, thermal stability, and processing performance, thereby enhancing the capacity, cycle life, and safety of the lithium-ion battery.
[0006] Therefore, the first aspect of the present invention provides a method for preparing a high-temperature resistant PI lithium battery porous separator, the method comprising the following steps: The first spirocyclic compound, the bicyclic orthoester, the dianhydride compound, and the diamine compound are brought into contact and polymerized to obtain a polyamic acid solution. The polyamic acid solution, pore-forming agent, second spirocyclic compound and photoinitiator are mixed, and a porous polyamic acid membrane is obtained by phase separation pore formation and photocrosslinking reaction; The porous polyamic acid membrane is subjected to imidization treatment to obtain the high-temperature resistant PI lithium battery porous membrane.
[0007] The preparation method provided by this invention introduces spirocyclic groups and bicyclic orthoester groups into the main chain and end groups of polyamic acid, respectively, during the polymerization reaction. After phase separation to form a porous membrane, the introduced spirocyclic groups and bicyclic orthoester groups are used as crosslinking sites for photocrosslinking and curing. The spirocyclic compound and bicyclic orthoester are expanding monomers and do not experience volume shrinkage during polymerization. Subsequent photocrosslinking with the second spirocyclic compound further fixes the pores in the membrane and improves the mechanical properties, thermal stability, and processability of the PI membrane, thereby enhancing the capacity, cycle life, and safety of the lithium battery.
[0008] According to an embodiment of the present invention, the molar ratio of the dianhydride compound to the total molar ratio of the first spirocyclic compound, the bicyclic orthoester, and the diamine compound is 1:(0.95-1.05).
[0009] According to an embodiment of the present invention, the molar ratio of the diamine compound, the first spirocyclic compound, and the bicyclic orthoester is 1:(0.01-0.1):(0.01-0.1).
[0010] According to an embodiment of the present invention, the first spirocyclic compound contains two amino groups.
[0011] According to an embodiment of the present invention, the first spirocyclic compound includes at least one of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine, 1,4,6,9-tetraoxaspiro[4,4]nonane-2,7-dimethyleneamine, and 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-dipropylamine.
[0012] According to an embodiment of the present invention, the bicyclic orthoester structure contains a single amino group.
[0013] According to embodiments of the present invention, the bicyclic orthoester comprises at least one selected from 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine, 3-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-1-amine, 4-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)butane-2-amine, 3-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-1-amine, 4-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octan-1-yl)butane-2-amine, 2,6,7-trioxabicyclo[2.2.2]octan-1-ethylamine, and 1-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-2-amine.
[0014] According to embodiments of the present invention, the dianhydride compound includes at least one selected from pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 4,4'-oxophthalic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,3',4,4'-triphenyl diether tetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride, and bisphenol A type diether dianhydride.
[0015] According to embodiments of the present invention, the diamine compound includes at least one selected from p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminobiphenyl, 3,5'-diaminobenzoic acid, 4,4'-diaminophenyl sulfone, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, and 4,4'-bis(3-aminophenoxy)biphenyl.
[0016] According to an embodiment of the present invention, the temperature of the polymerization reaction is 0 ℃-50 ℃.
[0017] According to an embodiment of the present invention, the polymerization reaction takes 0.5 h to 5 h.
[0018] According to an embodiment of the present invention, the preparation method further includes: contacting a first spirocyclic compound, a bicyclic orthoester, a dianhydride compound, a diamine compound, and a solvent to carry out a polymerization reaction to obtain a polyamic acid solution.
[0019] According to an embodiment of the present invention, the mass percentage of the solvent in the polyamic acid solution is 50 wt%-95 wt%.
[0020] According to embodiments of the present invention, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0021] According to an embodiment of the present invention, the mass ratio of the polyamic acid solution, the pore-forming agent, the second spirocyclic compound, and the photoinitiator is 1:(0.05-0.3):(0.001-0.01):(0.001-0.01).
[0022] According to embodiments of the present invention, the pore-forming agent includes at least one selected from dioctyl phthalate, polyvinylpyrrolidone-K17, polyvinylpyrrolidone-K30, polyethylene glycol 400, diethylene glycol, triethylene glycol, and glycerol.
[0023] According to an embodiment of the present invention, the second spirocyclic compound includes at least one selected from 3,9-dihydroxymethyl-3',9'-diethyl-1,5,7,11-tetraoxaspiro[5,5]undecane, 1,5,7,11-tetraoxaspiro[5.5]undecane, 8,10,19,20-tetraoxatrispiro[5.2.2.5.2]eicosane, 2,2'-spirocyclic bis[1,3-benzodioxane], and 1,4,6,9-tetraoxaspiro[4.4]nonane.
[0024] According to embodiments of the present invention, the photoinitiator includes at least one selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylpropanone, and 1,1'-(oxydi(4,1-phenylene))di(2-hydroxy-2-methyl-1-propanone).
[0025] According to an embodiment of the present invention, the mixing temperature is 0 ℃-30 ℃.
[0026] According to an embodiment of the present invention, the mixing is carried out under light-proof, nitrogen atmosphere conditions.
[0027] According to an embodiment of the present invention, the preparation method further includes: adding a pore-forming agent, a second spirocyclic compound and a photoinitiator to a polyamic acid solution, stirring until homogeneous, to obtain a casting solution.
[0028] According to an embodiment of the present invention, the preparation method further includes: under light-protected conditions, coating the casting solution onto the base film with a doctor blade to obtain a wet film; immersing the wet film in a coagulation bath to achieve phase separation and pore formation; then irradiating the polyamic acid film with ultraviolet light under nitrogen protection to initiate a photocrosslinking reaction; drying the crosslinked film; peeling it off from the base film; and then winding it to obtain a rolled porous polyamic acid film.
[0029] According to embodiments of the present invention, the base film includes, but is not limited to, polyethylene terephthalate film, polyethylene film, or polypropylene film.
[0030] According to an embodiment of the present invention, the release force of the base film is 5 g / mm-100 g / mm.
[0031] According to an embodiment of the present invention, the coating thickness is 25 μm-200 μm.
[0032] According to an embodiment of the present invention, the coagulation bath comprises water and alcohol.
[0033] According to an embodiment of the present invention, the volume ratio of water to alcohol is 1:(0.05-1).
[0034] According to embodiments of the present invention, the alcohol includes at least one of ethanol, methanol, and isopropanol.
[0035] According to an embodiment of the present invention, the coagulation bath is prepared in one manner.
[0036] According to an embodiment of the present invention, the coagulation bath is prepared in various ways and the ingredients are soaked in it sequentially.
[0037] According to an embodiment of the present invention, the soaking time is 0.5 min to 10 min for each coagulation bath.
[0038] According to an embodiment of the present invention, the soaking temperature is 10 ℃-30 ℃.
[0039] According to an embodiment of the present invention, the drying temperature is 50 ℃-100 ℃.
[0040] According to an embodiment of the present invention, the drying time is 1 min to 10 min.
[0041] According to an embodiment of the present invention, the temperature of the photocrosslinking reaction is 10 ℃-30 ℃.
[0042] According to an embodiment of the present invention, the photocrosslinking reaction takes 0.5 min to 5 min.
[0043] According to an embodiment of the present invention, the light source for the photocrosslinking reaction includes ultraviolet light.
[0044] According to an embodiment of the present invention, the energy of the ultraviolet light is 100 mJ / cm². 2 -1500 mJ / cm 2 .
[0045] According to an embodiment of the present invention, the imidization treatment temperature is 100 ℃-350 ℃.
[0046] According to an embodiment of the present invention, the imidization treatment time is 0.5 h to 5 h.
[0047] The second aspect of the present invention provides a high-temperature resistant PI lithium battery porous separator obtained according to the preparation method described in the first aspect.
[0048] The high-temperature resistant PI lithium battery porous membrane can be prepared by the preparation method provided by the present invention. The membrane has the advantages of good mechanical properties and high thermal stability. At the same time, the membrane has high porosity and complete pores.
[0049] According to an embodiment of the present invention, the thickness of the high-temperature resistant PI lithium battery porous separator is 5 μm-25 μm.
[0050] A third aspect of the present invention provides a secondary battery comprising a high-temperature resistant PI lithium battery porous membrane obtained by the preparation method described in the first aspect or the high-temperature resistant PI lithium battery porous membrane described in the second aspect.
[0051] The secondary battery made using the high-temperature resistant PI lithium battery porous separator provided by this invention has excellent capacity, cycle life and safety.
[0052] The advantages of this invention over the prior art are: (1) Excellent processing performance: A cross-linked high-temperature resistant PI lithium battery porous membrane is obtained by photocrosslinking the spirocyclic groups and bicyclic orthoester groups in the PAA chain segment with the second spirocyclic compound, followed by imidization treatment. The mechanical properties are improved after crosslinking, and the pores are fixed. In subsequent drying, peeling, and winding processes, the cross-linked membrane is not easily damaged and can withstand greater traction tension and peeling force. Crosslinking reduces the volume shrinkage effect of the PAA membrane during imidization treatment, which is beneficial to the integrity of the pores and the membrane.
[0053] (2) Excellent performance: The mechanical properties of the cross-linked high-temperature resistant PI lithium-ion battery porous membrane are improved. During subsequent battery manufacturing processes, the rolled membrane needs to be unrolled again, and the cross-linked PI polymer can withstand greater traction tension. Cross-linking also increases the heat resistance of the high-temperature resistant PI lithium-ion battery porous membrane. Simultaneously, the integrity of the pores gives the membrane good ion permeability, reducing battery internal resistance; good resistance to electrochemical corrosion; good stability in the electrolyte; and good electrolyte wettability. This improves both the electrochemical performance and safety performance of the lithium battery.
[0054] (3) Low process cost and wide applicability: The preparation process of introducing expanded monomer crosslinking has low equipment requirements. By adjusting the type and ratio of monomers, the performance requirements of different products can be met, and the method has wide applicability.
[0055] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0056] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0057] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0058] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0059] To facilitate understanding of the invention, certain technical and scientific terms are specifically defined below. Unless otherwise expressly defined elsewhere in this document, all other technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art to which this invention pertains.
[0060] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this invention, but do not exclude other aspects.
[0061] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0062] The term "expanding monomer" refers to a class of monomeric substances whose volume expands or decreases during polymerization (normal monomers shrink in volume after polymerization). Expanding monomers mainly include spirocyclic orthocarbonates (SOC), spirocyclic orthoesters (SOE), and bicyclic orthoesters (BOE).
[0063] According to embodiments of the present invention, a first aspect provides a method for preparing a high-temperature resistant PI lithium battery porous separator, the method comprising the following steps: (1) The first spirocyclic compound, the bicyclic orthoester, the dianhydride compound, and the diamine compound are brought into contact and polymerized to obtain a polyamic acid solution.
[0064] In step (1), in addition to using common dianhydride compounds and diamine compounds, a first spirocyclic compound and a bicyclic orthoester are also used in the synthesis of PAA. The spirocyclic group and the bicyclic orthoester group are introduced into the segments and ends of the PAA chain, respectively. The spirocyclic group and the bicyclic orthoester group will serve as the crosslinking points for the subsequent photocrosslinking reaction.
[0065] Specifically, in the polymerization reaction, the monomers polymerize randomly.
[0066] According to specific embodiments of the present invention, the molar ratio of the diacid anhydride compound to the total molar ratio of the first spirocyclic compound, the bicyclic orthoester, and the diamine compound is 1:(0.95-1.05). As some specific examples, the molar ratio of the diacid anhydride compound to the total molar ratio of the first spirocyclic compound, the bicyclic orthoester, and the diamine compound may be 1:0.95, 1:1, 1:1.05, etc.
[0067] According to specific embodiments of the present invention, the molar ratio of the diamine compound, the first spirocyclic compound, and the bicyclic orthoester is 1:(0.01-0.1):(0.01-0.1). As some specific examples, the molar ratio of the diamine compound, the first spirocyclic compound, and the bicyclic orthoester may be 1:0.01:0.01, 1:0.01:0.1, 1:0.1:0.01, 1:0.1:0.1, etc.
[0068] According to a specific embodiment of the present invention, the first spirocyclic compound contains two amino groups in its structure. The type of the first spirocyclic compound is not particularly limited; as some specific examples, the first spirocyclic compound includes at least one of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine (CAS: 1379509-69-9), 1,4,6,9-tetraoxaspiro[4,4]nonane-2,7-dimethyleneamine (CAS: 1379509-68-8), and 1,5,7,11-tetraoxaspiro[5.5]undecane-3,9-dipropylamine (CAS: 118432-48-7).
[0069] Specifically, the two amino groups in the first spirocyclic compound can react with the diacid anhydride compound, thereby introducing spirocyclic groups into the PAA chain segment.
[0070] According to specific embodiments of the present invention, the bicyclic orthoester structure contains a single amino group. The type of bicyclic orthoester is not particularly limited; as some specific examples, the bicyclic orthoester includes 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine (CAS: 1893887-68-7), 3-(2,6,7-trioxabicyclo[2.2.2]octane-1-yl)propane-1-amine (CAS: 1896790-05-8), 4-(2,6,7-trioxabicyclo[2.2.2]octane-1-yl)butane-2-amine (CAS: 1892374-20-7), 3-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octane-1-yl)butane-2-amine, etc. At least one of the following: cyclo[2.2.2]octane-1-yl)prop-1-amine (CAS: 1893947-48-2), 4-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octane-1-yl)but-2-amine (CAS: 1893258-44-0), 2,6,7-trioxabicyclo[2.2.2]octane-1-ethylamine (CAS: 1893887-72-3), and 1-(2,6,7-trioxabicyclo[2.2.2]octane-1-yl)prop-2-amine (CAS: 1894564-22-7).
[0071] Specifically, a single amino group in the bicyclic orthoester can react with a dianhydride compound to generate a capping group, introducing the bicyclic orthoester group to the end of the PAA.
[0072] According to specific embodiments of the present invention, the type of dianhydride compound is not particularly limited. As some specific examples, the dianhydride compound includes at least one selected from pyromellitic dianhydride (CAS: 89-32-7), 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (CAS: 2420-87-3), 4,4'-oxophthalic anhydride (CAS: 1823-59-2), 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride (CAS: 2421-28-5), 3,3',4,4'-triphenyl diether tetracarboxylic acid dianhydride (CAS: 17828-53-4), 3,3',4,4'-diphenyl sulfone tetracarboxylic acid dianhydride (CAS: 2540-99-0), and bisphenol A type diether dianhydride (CAS: 38103-06-9).
[0073] According to specific embodiments of the present invention, the type of diamine compound is not particularly limited. As some specific examples, the diamine compound includes p-phenylenediamine (CAS: 106-50-3), 4,4'-diaminodiphenyl ether (CAS: 101-80-4), 4,4'-diaminodiphenylmethane (CAS: 101-77-9), 4,4'-diaminobiphenyl (CAS: 92-87-5), and 3,5'-diaminobenzoic acid (CAS: 535- At least one of the following: 87-5), 4,4'-diaminophenyl sulfone (CAS: 80-08-0), 1,3-bis(4-aminophenoxy)benzene (CAS: 2479-46-1), 1,4-bis(4-aminophenoxy)benzene (CAS: 3491-12-1), 4,4'-bis(4-aminophenoxy)biphenyl (CAS: 13080-85-8), and 4,4'-bis(3-aminophenoxy)biphenyl (CAS: 105112-76-3).
[0074] According to specific embodiments of the present invention, the temperature of the polymerization reaction is 0 ℃-50 ℃. As some specific examples, the temperature of the polymerization reaction can be 0 ℃, 10 ℃, 20 ℃, 30 ℃, 40 ℃, 50 ℃, etc.
[0075] According to a specific embodiment of the present invention, the polymerization reaction time is 0.5 h-5 h. As some specific examples, the polymerization reaction time can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, etc.
[0076] According to a specific embodiment of the present invention, the preparation method further includes: contacting a first spirocyclic compound, a bicyclic orthoester, a dianhydride compound, a diamine compound, and a solvent to carry out a polymerization reaction to obtain a polyamic acid solution.
[0077] According to specific embodiments of the present invention, the mass percentage of the solvent in the polyamic acid solution is 50 wt%-95 wt%. As some specific examples, the mass percentage of the solvent in the polyamic acid solution may be 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt%, 95 wt%, etc.
[0078] According to specific embodiments of the present invention, the type of solvent is not particularly limited. As some specific examples, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0079] According to a specific embodiment of the present invention, the specific operation of step (1) can be as follows: dissolve the diamine compound, the first spirocyclic compound and the bicyclic orthoester in a solvent, add the dianhydride compound under nitrogen protection, and stir until the reaction is complete.
[0080] (2) The polyamic acid solution, pore-forming agent, second spirocyclic compound and photoinitiator are mixed and pore-forming and photocrosslinking reaction is carried out to obtain a porous polyamic acid membrane.
[0081] In step (2), in addition to the pore-forming agent, a photoinitiator and a second spirocyclic compound are introduced. The second spirocyclic compound will form cross-linked segments in the subsequent photocuring cross-linking reaction. During phase separation, the polymer-depleted phase forms pores, and the polymer-rich phase forms a framework. The photoinitiator and the second spirocyclic compound remain in the polymer-rich phase and undergo ring-opening polymerization with the spirocyclic groups and bicyclic orthoester groups in PAA through photoinitiation. After the photocuring cross-linking reaction, a cross-linked PAA porous membrane is obtained. Since the expanding monomers (i.e., spirocyclic compounds and bicyclic orthoesters) do not cause volume shrinkage during polymerization, the pore collapse caused by the shrinkage of the polymer framework during cross-linking is reduced, which is beneficial to the porosity and pore integrity of the membrane. After cross-linking, the pores of PAA are fixed. The mechanical properties of the polymer are also improved, the pores are not easy to collapse during drying, and the PAA membrane is not easy to break. In the subsequent winding process, a tensioning device is used. The tensile strength of the cross-linked PAA membrane is greater than that of the uncross-linked PAA membrane, and it can withstand greater internal stress, making the wound PAA membrane less prone to breakage. In addition, compared with thermally initiated crosslinking, photocuring crosslinking does not require heating, and the thermal effect during polymerization is smaller, which will not cause drastic changes in the wet film volume or wrinkling, thus helping to maintain the flatness of the film.
[0082] According to specific embodiments of the present invention, the mass ratio of the polyamic acid solution, pore-forming agent, second spirocyclic compound, and photoinitiator is 1:(0.05-0.3):(0.001-0.01):(0.001-0.01). As some specific examples, the mass ratio of the polyamic acid solution, pore-forming agent, second spirocyclic compound, and photoinitiator may be 1:0.05:0.001:0.001, 1:0.3:0.01:0.01, etc.
[0083] According to specific embodiments of the present invention, the type of pore-forming agent is not particularly limited. As some specific examples, the pore-forming agent includes at least one selected from dioctyl phthalate, polyvinylpyrrolidone-K17, polyvinylpyrrolidone-K30, polyethylene glycol 400, diethylene glycol, triethylene glycol, and glycerol.
[0084] According to specific embodiments of the present invention, the type of the second spirocyclic compound is not particularly limited. As some specific examples, the second spirocyclic compound includes at least one of 3,9-dihydroxymethyl-3',9'-diethyl-1,5,7,11-tetraoxaspiro[5,5]undecane (CAS: 65282-19-1), 1,5,7,11-tetraoxaspiro[5.5]undecane (CAS: 24472-02-4), 8,10,19,20-tetraoxatrispiro[5.2.2.5.2]eicosane (CAS: 57565-08-9), 2,2'-spirocyclic bis[1,3-benzodioxane] (CAS: 181-82-8), and 1,4,6,9-tetraoxaspiro[4.4]nonane (CAS: 24471-99-6).
[0085] Specifically, the second spirocyclic compound does not contain amino groups and only participates in the subsequent photocuring crosslinking reaction.
[0086] According to specific embodiments of the present invention, the type of photoinitiator is not particularly limited. As some specific examples, the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173, CAS No.: 7473-98-5), 1-hydroxycyclohexylphenyl ketone (photoinitiator 184, CAS No.: 947-19-3), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO, CAS No.: 75980-60-8), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylpropanone (photoinitiator 2959, CAS No.: 106797-53-9), and 1,1'-(oxydi(4,1-phenylene))di(2-hydroxy-2-methyl-1-propanone) (photoinitiator 160, CAS No.: 71868-15-0).
[0087] According to a specific embodiment of the present invention, the mixing temperature is 0 ℃-30 ℃. As some specific examples, the mixing temperature may be 0 ℃, 10 ℃, 20 ℃, 30 ℃, etc.
[0088] According to a specific embodiment of the present invention, the specific operation of step (2) can be as follows: under light-proof and nitrogen atmosphere conditions, add pore-forming agent, second spirocyclic compound and photoinitiator to PAA solution, stir evenly to obtain casting solution; under light-proof conditions, apply casting solution to base film with a doctor blade to obtain wet film, immerse wet film in coagulation bath to achieve phase separation and pore formation, then under nitrogen protection, irradiate PAA film with ultraviolet light to initiate photocrosslinking reaction, dry crosslinked film, peel off from base film, and obtain rolled porous PAA film through winding process.
[0089] According to specific embodiments of the present invention, the type of base film is not particularly limited, and as some specific examples, it includes, but is not limited to, polyethylene terephthalate (PET) film, polyethylene (PE) film, and polypropylene (PP) film.
[0090] According to specific embodiments of the present invention, the release force of the base film is 5 g / mm-100 g / mm. As some specific examples, the release force of the base film can be 5 g / mm, 10 g / mm, 20 g / mm, 50 g / mm, 100 g / mm, etc.
[0091] According to specific embodiments of the present invention, the coating thickness is 25 μm-200 μm. As some specific examples, the coating thickness can be 25 μm, 50 μm, 100 μm, 150 μm, 200 μm, etc.
[0092] According to a specific embodiment of the present invention, the coagulation bath comprises water and alcohol.
[0093] According to specific embodiments of the present invention, the volume ratio of water to alcohol is 1:(0.05-1). As some specific examples, the volume ratio of water to alcohol may be 1:0.05, 1:0.1, 1:0.2, 1:0.5, 1:1, etc. The type of alcohol is not particularly limited, and as some specific examples, it includes, but is not limited to, ethanol, methanol, and isopropanol.
[0094] According to a specific embodiment of the present invention, the coagulation bath is prepared in one manner.
[0095] According to a specific embodiment of the present invention, the coagulation bath is prepared in various ways and the ingredients are soaked in it sequentially.
[0096] According to specific embodiments of the present invention, the soaking time is 0.5 min to 10 min for each coagulation bath. As some specific examples, the soaking time is 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc. for each coagulation bath.
[0097] According to specific embodiments of the present invention, the soaking temperature is 10 ℃-30 ℃. As some specific examples, the soaking temperature is 10 ℃, 15 ℃, 20 ℃, 25 ℃, 30 ℃, etc.
[0098] According to specific embodiments of the present invention, the drying temperature is 50℃-100℃. As some specific examples, the drying temperature can be 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, etc. The drying time is 1min-10min. As some specific examples, the drying time can be 1min, 2min, 3min, 5min, 8min, 10min, etc.
[0099] According to a specific embodiment of the present invention, the temperature of the photocrosslinking reaction is 10 ℃-30 ℃. As some specific examples, the temperature of the photocrosslinking reaction can be 10 ℃, 15 ℃, 20 ℃, 25 ℃, 30 ℃, etc.
[0100] According to a specific embodiment of the present invention, the photocrosslinking reaction time is 0.5 min to 5 min. As some specific examples, the photocrosslinking reaction time can be 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, etc.
[0101] According to specific embodiments of the present invention, the light source for the photocrosslinking reaction is not particularly limited, and includes, but is not limited to, ultraviolet light.
[0102] According to a specific embodiment of the present invention, the energy of the ultraviolet light is 100 mJ / cm². 2 -1500 mJ / cm 2 As some specific examples, the energy of the ultraviolet light can be 100 mJ / cm². 2 200 mJ / cm 2 300 mJ / cm 2 500 mJ / cm 2 1000 mJ / cm 2 1500 mJ / cm 2 wait.
[0103] (3) The porous polyamic acid membrane is subjected to imidization treatment to obtain the high temperature resistant PI lithium battery porous membrane.
[0104] In step (3), since the PAA membrane has already been cross-linked, the volume shrinkage effect caused by the imidization treatment will be reduced, making the PAA less prone to breakage during the imidization treatment. When using the rolled PI membrane, it is necessary to unroll the PI membrane again, as the cross-linked PI polymer can withstand greater traction tension.
[0105] According to specific embodiments of the present invention, the imidization treatment temperature is 100 ℃-350 ℃. As some specific examples, the imidization treatment temperature can be 100 ℃, 200 ℃, 300 ℃, 350 ℃, etc. Specifically, a gradient heating method can be adopted.
[0106] According to a specific embodiment of the present invention, the imidization treatment time is 0.5 h-5 h. As some specific examples, the imidization treatment time can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, etc.
[0107] According to a specific embodiment of the present invention, the imidization treatment includes: under nitrogen protection, placing the rolled PAA film in a high-temperature environment and gradually increasing the temperature, holding it at temperature T1 for 0.5-2 h, holding it at temperature T2 for 0.5-2 h, holding it at temperature T3 for 0.5-2 h, and then cooling it down to obtain a high-temperature resistant PI lithium battery porous separator; wherein T3 > T2 > T1.
[0108] According to a specific embodiment of the present invention, the imidization treatment is carried out under an inert atmosphere, for example, under a nitrogen atmosphere.
[0109] According to an embodiment of the present invention, a second aspect of the present invention provides a high-temperature resistant PI lithium battery porous separator obtained according to the preparation method described in the first aspect.
[0110] The high-temperature resistant PI lithium battery porous membrane can be prepared by the preparation method provided by the present invention. The membrane has the advantages of good mechanical properties and high thermal stability. At the same time, the membrane has high porosity and complete pores.
[0111] According to specific embodiments of the present invention, the thickness of the high-temperature resistant PI lithium battery porous separator is 5 μm-25 μm. As some specific examples, the thickness of the high-temperature resistant PI lithium battery porous separator can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, etc.
[0112] According to an embodiment of the present invention, a third aspect of the present invention provides a secondary battery, the secondary battery comprising a high-temperature resistant PI lithium battery porous separator obtained according to the preparation method described in the first aspect or the high-temperature resistant PI lithium battery porous separator described in the second aspect.
[0113] The secondary battery made using the high-temperature resistant PI lithium battery porous separator provided by this invention has excellent capacity, cycle life and safety.
[0114] According to a specific embodiment of the present invention, the secondary battery further includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector, the positive active material layer including a positive active material; The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate, and nickel-cobalt-manganese ternary materials. Typically, a battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0115] In some embodiments of the present invention, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0116] In some embodiments of the present invention, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, conductive carbon black SP, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some embodiments of the present invention, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0118] In some embodiments of the present invention, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, and binder, in a solvent (e.g., N-methylpyrrolidone, NMP) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0119] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector, wherein the negative active material layer includes a negative active material.
[0120] In some embodiments of the present invention, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0121] In some embodiments of the present invention, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, nano-carbon, elemental silicon, silicon oxide, silicon-carbon composite, silicon alloy, elemental tin, tin oxide, tin-carbon composite, tin alloy, and lithium titanate.
[0122] In some embodiments of the present invention, the negative electrode active material layer may optionally include a binder. The binder may include at least one selected from styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0123] In some embodiments of the present invention, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0124] In some embodiments of the present invention, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0125] In some embodiments of the present invention, the negative electrode active material layer may optionally include other additives, such as dispersants (e.g., Electro-Rite BD040).
[0126] In some embodiments of the present invention, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, dispersant, conductive agent, binder and thickener, in a solvent (e.g. water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0127] In some embodiments of the present invention, the above-mentioned separator is wound with positive and negative electrode sheets to obtain a lithium-ion secondary battery.
[0128] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0129] Example 1 This embodiment provides a high-temperature resistant PI lithium battery porous separator and its preparation method, the preparation method including the following steps: PAA Synthesis: 82.62 g of 4,4'-diaminodiphenyl ether (diamine compound), 4.36 g of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine (first spirocyclic compound), and 3.33 g of 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine (bicyclic orthoester) were dissolved in 800 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of pyromellitic dianhydride (dianhydride compound) was added, and the mixture was stirred for 3 h until the reaction was complete to obtain an NMP solution containing PAA. Preparation of casting solution: Under light-protected conditions, at 10 °C and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent), 5 g of 1,5,7,11-tetraoxaspiro[5.5]undecane (second spirocyclic compound) and 5 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator) to 1 kg of NMP solution containing PAA, stir until homogeneous, and obtain the casting solution; Wet film coating: Under light-protected conditions, the casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇 Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under light-protected conditions at 25 ℃, the wet film was sequentially immersed in coagulation bath 1 for 5 min, and then immersed in coagulation bath 2 for 5 min. Photocuring crosslinking: Under nitrogen protection, at 25℃, using an energy of 1000 mJ / cm 2 The PAA film was irradiated with ultraviolet light for 1 minute; Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET base film and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a high-temperature resistant PI lithium battery porous separator is obtained.
[0130] The specific reaction process in this embodiment can be referred to the following reaction formula. Since the monomers in the polymerization reaction are randomly polymerized, the monomer letter subscripts in the reaction formula only represent repeating units.
[0131]
[0132] Example 2 The difference between this embodiment and Example 1 is that the types of the first spirocyclic compound and the bicyclic orthoester have been changed. The specific preparation process is as follows: PAA Synthesis: 82.62 g of 4,4'-diaminodiphenyl ether (diamine compound), 6.29 g of 1,5,7,11-tetraoxaspiro[5.5]undecane-3,9-dipropylamine (first spirocyclic compound) and 3.97 g of 3-(2,6,7-trioxabicyclo[2.2.2]octane-1-yl)propane-1-amine (bicyclic orthoester) were dissolved in 800 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of pyromellitic dianhydride (dianhydride compound) was added, and the mixture was stirred for 3 h until the reaction was complete to obtain an NMP solution containing PAA. Preparation of casting solution: Under light-protected conditions, at 10 °C and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent), 5 g of 1,5,7,11-tetraoxaspiro[5.5]undecane (second spirocyclic compound) and 5 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator) to 1 kg of NMP solution containing PAA, stir until homogeneous, and obtain the casting solution; Wet film coating: Under light-protected conditions, the casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under light-protected conditions at 25 ℃, the wet film was sequentially immersed in coagulation bath 1 for 5 min, and then immersed in coagulation bath 2 for 5 min. Photocuring crosslinking: Under nitrogen protection, at 25℃, using an energy of 1000 mJ / cm 2 The PAA film was irradiated with ultraviolet light for 1 minute; Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET base film and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a high-temperature resistant PI lithium battery porous separator is obtained.
[0133] Example 3 The difference between this embodiment and Example 1 is that the type of the second spirocyclic compound has been changed. The specific preparation process is as follows: PAA Synthesis: 82.62 g of 4,4'-diaminodiphenyl ether (diamine compound), 4.36 g of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine (first spirocyclic compound), and 3.33 g of 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine (bicyclic orthoester) were dissolved in 800 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of pyromellitic dianhydride (dianhydride compound) was added, and the mixture was stirred for 3 h until the reaction was complete to obtain an NMP solution containing PAA. Preparation of casting solution: Under light-protected conditions, at 10 °C, and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent), 5 g of 1,4,6,9-tetraoxazolo[4.4]nonane (second spirocyclic compound), and 5 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator) to 1 kg of NMP solution containing PAA, and stir until homogeneous to obtain the casting solution; Wet film coating: Under light-protected conditions, the casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇 Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under light-protected conditions at 25 ℃, the wet film was sequentially immersed in coagulation bath 1 for 5 min, and then immersed in coagulation bath 2 for 5 min. Photocuring crosslinking: Under nitrogen protection, at 25℃, using an energy of 1000 mJ / cm 2 The PAA film was irradiated with ultraviolet light for 1 minute; Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET substrate and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a high-temperature resistant PI lithium battery porous separator is obtained.
[0134] Example 4 The difference between this embodiment and Example 1 is that the types of diamine and dianhydride compounds have been changed. The specific preparation process is as follows: PAA Synthesis: 53.45 g of 4,4'-diaminobiphenyl (diamine compound), 3.07 g of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine (first spirocyclic compound), and 2.34 g of 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine (bicyclic orthoester) were dissolved in 750 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of 4,4'-oxophthalic anhydride (dianhydride compound) was added, and the mixture was stirred for 3 h until the reaction was complete to obtain an NMP solution containing PAA. Preparation of casting solution: Under light-protected conditions, at 10 °C and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent), 5 g of 1,5,7,11-tetraoxaspiro[5.5]undecane (second spirocyclic compound) and 5 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator) to 1 kg of NMP solution containing PAA, stir until homogeneous, and obtain the casting solution; Wet film coating: Under light-protected conditions, the casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇 Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under light-protected conditions at 25 ℃, the wet film was sequentially immersed in coagulation bath 1 for 5 min, and then immersed in coagulation bath 2 for 5 min. Photocuring crosslinking: Under nitrogen protection, at 25℃, using an energy of 1000 mJ / cm 2 The PAA film was irradiated with ultraviolet light for 1 minute; Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET substrate and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a high-temperature resistant PI lithium battery porous separator is obtained.
[0135] Comparative Example 1 This comparative example provides a polyimide separator and its preparation method, including the following steps: PAA synthesis: 91.8 g of 4,4'-diaminodiphenyl ether (diamine compound) was dissolved in 800 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of pyromellitic dianhydride (dianhydride compound) was added and stirred for 3 h until the reaction was complete to obtain an NMP solution containing PAA. Preparation of casting solution: Under light-protected conditions, at 10 °C and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent) to 1 kg of NMP solution containing PAA, stir until homogeneous, and obtain the casting solution; Wet film coating: The casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇 Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under 25 ℃ conditions, the wet film was immersed in coagulation bath 1 for 5 min, and then the wet film was immersed in coagulation bath 2 for 5 min. Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET substrate and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a polyimide separator is obtained.
[0136] Comparative Example 2 This comparative example provides a polyimide separator and its preparation method, including the following steps: PAA Synthesis: 82.62 g of 4,4'-diaminodiphenyl ether (diamine compound), 4.36 g of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine (first spirocyclic compound), and 3.33 g of 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine (bicyclic orthoester) were dissolved in 800 g of NMP solvent. Under nitrogen protection at 10 °C, 100 g of pyromellitic dianhydride (dianhydride compound) was added. The mixture was stirred for 3 h until the reaction was complete. An NMP solution containing PAA was obtained. Preparation of casting solution: Under light-protected conditions, at 10 °C and under nitrogen protection, add 150 g of dioctyl phthalate (pore-forming agent) to 1 kg of NMP solution containing PAA, stir until homogeneous, and obtain the casting solution; Wet film coating: Under light-protected conditions, the casting solution is coated onto a PET base film with a release force of 50 g / mm using a doctor blade, and the wet film thickness is 100 μm; Preparation of coagulation bath: by volume ratio V 水 V 乙醇 Prepare coagulation bath 1 with a volume ratio of 1:1 (V). 水 V 乙醇 Prepare coagulation bath 2:1; Phase separation pore formation: Under 25 ℃ conditions, the wet film was immersed in coagulation bath 1 for 5 min, and then the wet film was immersed in coagulation bath 2 for 5 min. Peeling the PET film: After the cross-linked film is dried at 80 °C for 3 min, the PAA film is peeled off from the PET substrate and then wound to obtain a roll of PAA film. Imidification treatment: Under nitrogen protection, the rolled PAA film is placed in a high-temperature environment and heated in a gradient manner, holding at 150 ℃ for 30 min, 200 ℃ for 30 min, and 300 ℃ for 30 min. After cooling, a polyimide separator is obtained.
[0137] Test case The membranes prepared in the above embodiments and comparative examples were subjected to the following performance tests: (1) Finished product thickness test: Shanghai Liuling CH-1-ST 1000 desktop thin film thickness gauge was used.
[0138] (2) Tensile strength and elongation at break test: The INSTRON tensile testing machine was used. The specimen was made into a sample with a width of 3 cm and a length of about 10 cm. The pulling speed was 2 mm / s.
[0139]
[0140] (3) Puncture strength test: The sample was cut into a square of 10 cm × 10 cm, and the maximum load of the steel needle puncture was recorded.
[0141] (4) Air permeability test: Use a GURLEY air permeability meter and timer to measure the time it takes for 100 ml of gas to penetrate the diaphragm.
[0142] (5) Porosity test: The porosity was measured using the gravimetric method. The diaphragm sample was immersed in a n-butanol solution for 4 hours. After the solution was saturated, the sample was removed, and excess n-butanol on the surface was absorbed with filter paper. The porosity was calculated by comparing the weight difference before and after immersion.
[0143] (6) Contact angle test: The test was conducted using a compound electrolyte, which was ethylene carbonate: methyl ethyl carbonate: diethyl carbonate = 3:5:2 (volume ratio).
[0144] (7) Heat shrinkage rate test: The sample was cut into a square of 10 cm × 10 cm and placed in a nitrogen-protected environment at 200 ℃ for 1 h. The change rate of its area was measured.
[0145] The performance test data of the diaphragms prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0146] Table 1
[0147] Batteries were prepared using the separators obtained in Examples 1-4 and Comparative Examples 1-2. The preparation methods for the batteries are as follows: Positive electrode preparation: Under nitrogen protection, 2 parts PVDF, 60 parts lithium iron phosphate, and 1 part conductive carbon black SP were uniformly dispersed in 37 parts NMP by mass percentage, and stirred to obtain a positive electrode slurry. The slurry was coated on aluminum foil, and the obtained positive electrode was placed in a vacuum drying oven and dried at 100 °C for 30 min. After rolling, the positive electrode sheet was obtained. Negative electrode preparation: By mass percentage, 97 parts of artificial graphite, 0.1 parts of dispersant (Electro-RiteBD040), 1 part of SBR binder, 1 part of carbon nanotubes, and 1 part of sodium carboxymethyl cellulose (CMC-Na) were uniformly dispersed in water and stirred to form a homogenate, thus obtaining a negative electrode slurry. The slurry was coated onto copper foil, and the obtained negative electrode was dried in a vacuum drying oven at 100 °C for 30 min to obtain the negative electrode sheet. The separators prepared in Examples 1-4 and Comparative Examples 1-2 were wound with positive and negative electrode sheets respectively to obtain 26650 cylindrical lithium-ion secondary batteries.
[0148] The secondary batteries prepared above were tested using the following methods, and the test results are shown in Table 2: Cyclic testing was conducted at 25 °C, with an operating voltage range of 1.5-3.0 V and current densities of 0.5C, 1C, and 2C, for 100 cycles. Discharge retention rate = (100th discharge capacity ÷ 1st discharge capacity) × 100%.
[0149] Table 2
[0150] Results analysis: As shown in Tables 1 and 2, the thicknesses of the membranes prepared in Examples 1-4 and Comparative Examples 1-2 are the same or not significantly different. Examples 1-4 improved the mechanical properties of the membranes through a crosslinking reaction. Specifically, the tensile strength of Examples 1-4 is greater than that of the uncrosslinked comparative examples, and their elongation at break is also greater, indicating that the toughness of the membranes prepared in these examples is also improved. Simultaneously, their puncture resistance is also superior to that of the uncrosslinked comparative examples.
[0151] By comparing the measured air permeability values, the air permeability of the embodiment is superior to that of the comparative example. The ease with which gas passes through the pores indirectly indicates that ions can more easily pass through the separator of the embodiment, which is beneficial for reducing the internal resistance of the battery. It also shows that the pores of the embodiment remain intact during drying, peeling, winding, and imidization processes, without collapse, damage, or blockage. The cross-linking reaction effectively fixes the pore structure, which is beneficial for subsequent processing steps and also for separator performance. Furthermore, the porosity measurement also corroborates the above points.
[0152] Contact angle tests show that after ring-opening crosslinking, spirocyclic compounds and bicyclic orthoesters form flexible segments, which enhance the electrolyte-loving properties of the separator, facilitate electrolyte wetting, and improve the cycle performance of the battery.
[0153] Measurements of heat shrinkage showed that the shrinkage of cross-linked Examples 1-4 was less than that of uncross-linked Comparative Examples 1-2, indicating that the cross-linking reaction can improve the heat resistance of the membrane material.
[0154] Through battery cycle testing, Examples 1-4 outperformed Comparative Examples 1-2 at 0.5C, 1C, and 2C rates, demonstrating that the improved separator preparation method can effectively improve the performance of lithium batteries.
[0155] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0156] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a high-temperature resistant polyimide lithium battery porous separator, characterized in that, The preparation method includes the following steps: The first spirocyclic compound, the bicyclic orthoester, the dianhydride compound, and the diamine compound are brought into contact and polymerized to obtain a polyamic acid solution. The polyamic acid solution, pore-forming agent, second spirocyclic compound and photoinitiator are mixed, and a porous polyamic acid membrane is obtained by phase separation pore formation and photocrosslinking reaction; The porous polyamic acid membrane is subjected to imidization treatment to obtain the high-temperature resistant polyimide lithium battery porous membrane; In this process, spirocyclic groups and bicyclic orthoester groups are introduced into the main chain and end groups of polyamic acid, respectively, during the polymerization reaction. After phase separation to form a porous membrane, the introduced spirocyclic groups and bicyclic orthoester groups are used as crosslinking sites for photocrosslinking and curing. During phase separation, the polymer-depleted phase forms pores, while the polymer-rich phase forms a framework. The photoinitiator and the second spirocyclic compound remain in the polymer-rich phase and undergo ring-opening polymerization with the spirocyclic groups and bicyclic orthoester groups in the polyamic acid through photoinitiation.
2. The preparation method according to claim 1, characterized in that, The molar ratio of the dianhydride compound to the total molar ratio of the first spirocyclic compound, the bicyclic orthoester, and the diamine compound is 1:(0.95-1.05). The molar ratio of the diamine compound, the first spirocyclic compound, and the bicyclic orthoester is 1:(0.01-0.1):(0.01-0.1).
3. The preparation method according to any one of claims 1-2, characterized in that, The first spirocyclic compound contains two amino groups in its structure.
4. The preparation method according to claim 3, characterized in that, The first spirocyclic compound includes at least one of 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-diamine, 1,4,6,9-tetraoxaspiro[4,4]nonane-2,7-dimethyleneamine, and 1,5,7,11-tetraoxaspiro[5,5]undecane-3,9-dipropylamine.
5. The preparation method according to any one of claims 1-2, characterized in that, The bicyclic orthoester structure contains a single amino group.
6. The preparation method according to claim 5, characterized in that, The bicyclic orthoester comprises at least one of 2,6,7-trioxabicyclo[2.2.2]oct-1-ylmethylamine, 3-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-1-amine, 4-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)butane-2-amine, 3-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-1-amine, 4-(4-methyl-2,6,7-trioxabicyclo[2.2.2]octan-1-yl)butane-2-amine, 2,6,7-trioxabicyclo[2.2.2]octan-1-ethylamine, and 1-(2,6,7-trioxabicyclo[2.2.2]octan-1-yl)propane-2-amine; The dianhydride compound includes at least one of the following: pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxobisphthalic anhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-triphenyl diether tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, and bisphenol A type diether dianhydride; The diamine compound includes at least one selected from p-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminobiphenyl, 3,5'-diaminobenzoic acid, 4,4'-diaminophenyl sulfone, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, and 4,4'-bis(3-aminophenoxy)biphenyl.
7. The preparation method according to any one of claims 1-2, characterized in that, The polymerization reaction is carried out at a temperature of 0℃-50℃; The polymerization reaction takes 0.5 h to 5 h; The preparation method further includes: contacting a first spirocyclic compound, a bicyclic orthoester, a dianhydride compound, a diamine compound, and a solvent to carry out a polymerization reaction to obtain a polyamic acid solution; The mass percentage of the solvent in the polyamic acid solution is 50 wt%-95 wt%. The solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
8. The preparation method according to any one of claims 1-2, characterized in that, The mass ratio of the polyamic acid solution, pore-forming agent, second spirocyclic compound, and photoinitiator is 1:(0.05-0.3):(0.001-0.01):(0.001-0.01). The pore-forming agent includes at least one of dioctyl phthalate, polyvinylpyrrolidone-K17, polyvinylpyrrolidone-K30, polyethylene glycol 400, diethylene glycol, triethylene glycol, and glycerol. The second spirocyclic compound includes at least one of 3,9-dihydroxymethyl-3',9'-diethyl-1,5,7,11-tetraoxaspiro[5,5]undecane, 1,5,7,11-tetraoxaspiro[5.5]undecane, 8,10,19,20-tetraoxatrispiro[5.2.2.5.2]eicosane, 2,2'-spirocyclic bis[1,3-benzodioxane], and 1,4,6,9-tetraoxaspiro[4.4]nonane; The photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexylphenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylpropanone, and 1,1'-(oxydi(4,1-phenylene))di(2-hydroxy-2-methyl-1-propanone); The mixing temperature is 0 ℃-30 ℃.
9. The preparation method according to any one of claims 1-2, characterized in that, The mixing was carried out under light-protected, nitrogen atmosphere conditions; The preparation method further includes: adding a pore-forming agent, a second spirocyclic compound and a photoinitiator to a polyamic acid solution, stirring evenly to obtain a casting solution; The preparation method further includes: under light-protected conditions, coating the casting solution onto the base film with a doctor blade to obtain a wet film; immersing the wet film in a coagulation bath to achieve phase separation and pore formation; then irradiating the polyamic acid film with ultraviolet light under nitrogen protection to initiate a photocrosslinking reaction; drying the crosslinked film; peeling it off from the base film; and then winding it to obtain a rolled porous polyamic acid film. The base film includes, but is not limited to, polyethylene terephthalate film, polyethylene film, or polypropylene film; The release force of the base film is 5 g / mm-100 g / mm; The coating thickness is 25 μm-200 μm; The coagulation bath consists of water and alcohol; The volume ratio of water to alcohol is 1:(0.05-1); The alcohol includes at least one of ethanol, methanol, and isopropanol.
10. The preparation method according to claim 9, characterized in that, The coagulation bath is prepared in one manner.
11. The preparation method according to claim 9, characterized in that, The coagulation bath is prepared in various ways and the soaking is carried out sequentially; The soaking time is 0.5 min to 10 min for each coagulation bath; The soaking temperature is 10℃-30℃; The drying temperature is 50 ℃-100 ℃; The drying time is 1 min to 10 min; The temperature for the photocrosslinking reaction is 10 ℃-30 ℃; The photocrosslinking reaction takes 0.5 min to 5 min; The light source for the photocrosslinking reaction includes ultraviolet light; The energy of the ultraviolet light is 100 mJ / cm². 2 -1500 mJ / cm 2 .
12. The preparation method according to any one of claims 1-2, characterized in that, The imidization treatment temperature is 100 ℃-350 ℃; The imidization treatment time is 0.5 h to 5 h.
13. A high-temperature resistant polyimide lithium battery porous separator obtained by the preparation method according to any one of claims 1-12.
14. The high-temperature resistant polyimide lithium battery porous separator according to claim 13, characterized in that, The thickness of the high-temperature resistant polyimide lithium battery porous membrane is 5 μm-25 μm.
15. A secondary battery, characterized in that, The secondary battery comprises a high-temperature resistant polyimide lithium battery porous separator obtained by the preparation method according to any one of claims 1-12 or the high-temperature resistant polyimide lithium battery porous separator according to any one of claims 13-14.
Citation Information
Patent Citations
Microporous film for power storage device separator and power storage device separator making use of the same
CN101292378A
Mixture paste for negative electrode of lithium ion secondary battery, negative electrode for lithium ion secondary battery, method for producing negative electrode for lithium ion secondary battery, and lithium ion secondary battery
CN107925060A